2018
DOI: 10.1016/j.clinthera.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Lipids and Fetal Overgrowth: Making Fat from Fat

Abstract: There is increasing recognition that maternal glucose concentrations lower than those previously used for diagnosis of gestational diabetes mellitus (GDM) and targeted for treatment can result in excess fetal growth. Yet, mothers with GDM who appear to have optimal glycemic control and mothers with obesity and normal glucose tolerance still have a significantly increased risk for delivering infants who are large for gestational age, or even more importantly, who have increased adiposity at birth. What is less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 80 publications
3
80
0
Order By: Relevance
“…Although much of the focus on fetal growth has been through a glucocentric lens, there is increasing recognition that it is not only maternal glucose that contributes to fetal fat accretion and that triglycerides (TGs) and FFAs also play a significant role ( 35 39 ). Another unexpected twist in our earlier CGM data ( 29 ), during which women with obesity on a controlled diet demonstrated higher 24-h glycemic profiles, was that a single fasting TG measured once at ∼14–16 weeks in pregnancy correlated more strongly with NB %fat by skinfolds than any of the glycemic profiles by CGM.…”
Section: The Underappreciated Role Of Maternal Lipids As a Contributomentioning
confidence: 99%
See 1 more Smart Citation
“…Although much of the focus on fetal growth has been through a glucocentric lens, there is increasing recognition that it is not only maternal glucose that contributes to fetal fat accretion and that triglycerides (TGs) and FFAs also play a significant role ( 35 39 ). Another unexpected twist in our earlier CGM data ( 29 ), during which women with obesity on a controlled diet demonstrated higher 24-h glycemic profiles, was that a single fasting TG measured once at ∼14–16 weeks in pregnancy correlated more strongly with NB %fat by skinfolds than any of the glycemic profiles by CGM.…”
Section: The Underappreciated Role Of Maternal Lipids As a Contributomentioning
confidence: 99%
“…1 ). Lipid metabolism in pregnancy is also highly variable, partly related to the estrogen-induced influence of VLDL production in pregnancy and CM-TG in the diet, superimposed on the degree of maternal adipose tissue IR ( 31 , 39 ). The degree to which TGs and FFAs may contribute to fetal fat accretion has yet to be fully elucidated, but observations that maternal glucose does not solely explain fetal overgrowth support its future investigation as a therapeutic target.…”
Section: Targeting Who What and When To Prevent Adverse Pregnancy Omentioning
confidence: 99%
“…Moreover, offspring who were overgrown during fetal development (macrosomia) as a result of maternal obesity had impaired glucose tolerance, elevated fasting insulin level, as well as increased adiposity and metabolic diseases (Stanford et al . ; Barbour & Hernandez, ). Thus, maintaining proper vasculogenesis and placental function in obese mothers is a critical step for preventing metabolic dysfunction in their offspring (Bairagi et al .…”
Section: Introductionmentioning
confidence: 97%
“…Foetal development is in uenced by neonatal and maternal metabolism [34,35] , and in the present study, we analysed the effects of neonatal carnitine levels and amino acids on neonatal growth parameters. We found that cord blood glycine levels were correlated with GDM a .…”
Section: Discussionmentioning
confidence: 99%